2022
DOI: 10.1186/s40249-022-01046-z
|View full text |Cite
|
Sign up to set email alerts
|

Transmissibility of tuberculosis among students and non-students: an occupational-specific mathematical modelling

Abstract: Background Recently, despite the steady decline in the tuberculosis (TB) epidemic globally, school TB outbreaks have been frequently reported in China. This study aimed to quantify the transmissibility of Mycobacterium tuberculosis (MTB) among students and non-students using a mathematical model to determine characteristics of TB transmission. Methods We constructed a dataset of reported TB cases from four regions (Jilin Province, Xiamen City, Chux… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…Despite a reduction in TB-related mortalities following the implementation of short-course directly observed treatment, it remains a leading cause of death globally [6], with approximately 25% of the global population being infected [7]. Equally important, colleges and universities are at-risk populations [8] with prior research reporting TB outbreaks among students in Italy, China, and Northwest Ethiopia, often resulting from repeated exposure to untreated TB cases [9][10][11][12]. Research attributes the high TB prevalence in higher educational institutions to inadequate understanding and awareness about this disease [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Despite a reduction in TB-related mortalities following the implementation of short-course directly observed treatment, it remains a leading cause of death globally [6], with approximately 25% of the global population being infected [7]. Equally important, colleges and universities are at-risk populations [8] with prior research reporting TB outbreaks among students in Italy, China, and Northwest Ethiopia, often resulting from repeated exposure to untreated TB cases [9][10][11][12]. Research attributes the high TB prevalence in higher educational institutions to inadequate understanding and awareness about this disease [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…University students, the new generation of migrant workers, young freelancers, and prisoners are characterized by collective living, low income, poor living environment, heavy workload, etc. Recently, a study performed in four cities in China quantified the transmissibility of M. tuberculosis among students and non-students and found that TB transmissibility from the non-student to student population strongly influenced students ( 9 ). It can be concluded that these particular environmental and host conditions provide fertile ground for the outbreak and epidemic of TB in these populations ( 9–11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a study performed in four cities in China quantified the transmissibility of M. tuberculosis among students and non-students and found that TB transmissibility from the non-student to student population strongly influenced students (9). It can be concluded that these particular environmental and host conditions provide fertile ground for the outbreak and epidemic of TB in these populations (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…In HIV-positive patients, active tuberculosis is due to the reactivation of endogenous latent disease and reinfection with a new strain [5]. Epidemiological studies have shown that co-infection with HIV can increase the risk of reactivation of latent tuberculosis by a factor of 20, and is the strongest known risk factor for the progression of M. tuberculosis infection to active disease [6]. Furthermore, the WHO has indicated that tuberculosis, along with HIV, is the most deadly infectious disease in the world, with both diseases estimated to be responsible for approximately 1.5 million deaths in 2022 [4].…”
Section: Introductionmentioning
confidence: 99%